Threat and Vulnerability of Thermal Discomfort in Yogyakarta City - Fathurrohmah, Septiana; Ayu Candra Kurniati (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
The world’s attention to climate issues is increasing as the issue of global warming and climate change emerges. Several studies with the scope of cities and urban areas concluded that urban surface temperatures have an increasing trend. This phenomenon will have an impact on the thermal comfort of urban population. Yogyakarta City as one of the National Activity Centers (PKN), is experiencing rapid urban development and leads to become a metropolitan city so it needs to be studied regarding its thermal comfort. This research is intended to identify the potential and vulnerability of thermal discomfort in Yogyakarta City. The identification of potential discomfort is carried out using the Discomfort Index (DI) approach and the Land Surface Temperature (LST) value. Meanwhile, vulnerability is identified in the social aspects of population. Furthermore, the potential and vulnerability scores are assessed to get an overview of thermal discomfort mitigation priorities. Based on DI analysis, thermal discomfort is felt by more than 50% of the Yogyakarta’s residents and it is estimated that in the future will get worse. By looking at the distribution of LST values, the high potential for discomfort is in the city center and has expanded to the north and northeast. Meanwhile, areas with high vulnerability are located in the center and south side of Yogyakarta City. From the combined assessment of threat and vulnerability, the areas that are the top priority for mitigation are in the center of Yogyakarta City, which include 7 districts, namely Danurejan, Gedongtengen, Gondomanan, Jetis, Kraton, Ngampilan, and Pakualaman. The medium priority districts are Gondokusuman and Wirobrajan.